Creative tourism: opportunities for smaller places? - Richards, Greg (2019)
This paper aims to review the development of creativity in tourism, and analyses the potential role of smaller places in creative development. In the past, the role of creativity has been primarily analysed in larger cities. In recent years, more attention has been paid to the creative development of smaller cities and regions. We argue that smaller places should not attempt to emulate big city models of creative development, such as attracting the creative class, but should find their own creative mode based on using their endogenous resources, capacity building and bottom-up creativity. In this way they can avoid the ‘creativity trap’ of following generic creativity models and develop modes of creative tourism more appropriate to their size and capabilities.